Multivariate Statistical Analysis on Main Factors of Grassland Degradation in Ewenki Grassland in China - Changlin（长林） (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Grassland resources are not only an important part of regional economic development, but also play an important role in regional ecosystems. It is an important means of production for animal husbandry as well as an important ecological barrier for the natural environment. Based on the relevant data of grassland resources in the Ewenki grassland from 2005 to 2016, this paper applies the factor analysis method and the grey relational analysis method to analyze the main influencing factors of grassland degradation in the Ewenki grassland. The analysis results show that the vegetation coverage of the Ewenki grasslands has shown a steady upward trend on the whole in past ten years, while the proportion of fine forages has decreased year by year and the unreasonable human activities have led to the decline of grassland biomass. The analysis results of influencing factors showed that economic factors reflecting human activities were the main factors affecting grassland degradation in the Ewenki grassland, and their contribution rate was much higher than that of other factors.